Право дружини на утримання під час вагітності та в разі проживання з нею дитини у віці до трьох років - Євко, В. Ю.; Yevko, V. Y.; ORCID: http://orcid.org/0000-0001-5871-803X (Право і безпека – 2021. – № 4 (83). – С. 156-166, 2021)
Розглянуто проблеми здійснення вагітною жінкою та жінкою, з якою проживає дитина у віці до трьох років, свого права на утримання від чоловіка. Досліджено чинне сімейне законодавство, яке регулює права та обов’язки подружжя з утримання. Проаналізовано практику розгляду судами справ про надання утримання вагітній дружині та дружині, з якою проживає дитина у віці до трьох років. Визначено коло проблем, що виникають під час здійснення вагітною дружиною та жінкою, з якою проживає дитина у віці до трьох років, свого права на утримання від чоловіка – батька дитини, запропоновано їх рішення. The problems of exercising the right to maintenance from a man for a pregnant woman and a woman who a child under the age of three lives with were examined.The p urpose of the study is to formulate theoretical provisions and practical recommendations for the application of norms governing the exercise of a woman's right to maintenance.A comp arative legal method of research was used to determine the procedure for apregnant wife and the wife who the child under the age of three lives with to exercise the right to maintenance from the child's fa-ther -husband.The analysis of court cases on the recovery of alimony for the maintenance of a pregnant wife and / or wife who a child under the age of three lives with was carried out using the method of systematic analysis.A study of the current family law of Ukraine, which regu-lates the rights and obligations of spouses with respect to maintenance, and an analysis of the pra ctice of the courts in cases involving maintenance for a pregnant wife and a wifewho the child under three years lives with, concluded that the provisions of Art. 5 st. 84 of the FC of Ukraine makes it impossible for a pregnant wife to exercise her right to maintenance from her husband during pregnancy.It was emphasized that the court should assess the husband's abil-ity to provide financial assistance to his wife on the basis of astudy of a number of legal facts that characterize his financial situation.The author believes that all types of maintenance of family members and relatives, provided by the family legislation of Ukraine, have the same le-gal nature and require the same legal regulation.In view of this, it has been concluded that fail-ure by a husband to pay maintenance to a pregnant wife or a wife living with a child under three years oldmay be punished by liquidated damages (penalty), Art. 196 FC of Ukraine The lack of criminal liability for evasion of alimony for the maintenance of a pregnant wife and / or wife who the child under the age of three lives with is a gap in current legislation that should be eliminated by amending Art. 164 of the Criminal Code of Ukraine. Рассмотрены проблемы осуществления беременной и женщиной, с которой проживает ребенок в возрасте до трех лет, своего права на содержание от мужчины. Исследовано действующее семейное законодательство, регулирующее права и обязанности супругов по содержанию. Проанализирована практика рассмотрения судами дел о предоставлении содержания беременной жене и жене, с которой проживает ребенок в возрасте до трех лет. Определен круг проблем, возникающих при осуществлении беременной женой и женщиной, с которой проживает ребенок в возрасте до трех лет, своего права на содержание от мужа – отца ребенка, предложено их решение.
The right of the wife to maintenance during pregnancy and in the case of living with her child under the age of three
Право жены на содержание во время беременности и в случае проживания с ней ребенка в возрасте до трех лет
Євко, В. Ю. Право дружини на утримання під час вагітності та в разі проживання з нею дитини у віці до трьох років / Вікторія Юріївна Євко // Право і безпека – 2021. – № 4 (83). –Євко В. Ю. Право дружини на утримання під час вагітності та в разі проживання з нею дитини у віці до трьох років. Право і безпека. 2021. № 4 (83). С. 156–166. DOI: https://doi.org/10.32631/pb.2021.4.16. Yevko, V. Yu. (2021). The right of the wife to maintenance during pregnancy and in the case of living with her child under the age of three. Law and Safety, 4(83), 156–166. https://doi.org/10.32631/pb.2021.4.16.
Keywords: Цивільне право. Civil Law. Гражданское право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Сімейне право. Family law. Семейное право; шлюб; брак; marriage; право на утримання вагітної дружини; право на содержание беременной жены; right to support a pregnant wife; подружжя; супруги; married couple; право дружини на утримання; право жены на содержание; wife's right to maintenance; право на утримання дружини, з якою проживає дитина у віці до трьох років; аліменти; алименты; alimony; штраф; fine; неустойка; penalty; пеня; правове регулювання; правовое регулирование; legal regulation; законодавство; законодательство; legislation